1997
DOI: 10.1128/jvi.71.3.2241-2251.1997
|View full text |Cite
|
Sign up to set email alerts
|

Human CD4+ T-cell response to hepatitis delta virus: identification of multiple epitopes and characterization of T-helper cytokine profiles

Abstract: The T-cell-mediated immune response plays a crucial role in defense against hepatotropic viruses as well as in the pathogenesis of viral chronic hepatitides. However, very little is known about the role of specific T cells during hepatitis delta virus (HDV) infection in humans. In this study, the T-cell response to HDV in chronic hepatitis B virus (HBV) carriers with HDV superinfection was investigated at different levels. Analysis of peripheral blood mononuclear cell (PBMC) proliferation in response to a reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
66
0
2

Year Published

1998
1998
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(72 citation statements)
references
References 58 publications
4
66
0
2
Order By: Relevance
“…50 Another recent study revealed that the T-cell response to HDAg is related to the activity of HDV-induced liver disease. 13 These findings support the necessity of T-cell immunity to modulate the disease course of HDV infection. As shown by the T-cell proliferation and cytokine assay, the DNA vaccines against HDV did produce cellular immune response with a Th1 preference.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…50 Another recent study revealed that the T-cell response to HDAg is related to the activity of HDV-induced liver disease. 13 These findings support the necessity of T-cell immunity to modulate the disease course of HDV infection. As shown by the T-cell proliferation and cytokine assay, the DNA vaccines against HDV did produce cellular immune response with a Th1 preference.…”
Section: Discussionsupporting
confidence: 56%
“…12 A recent study showed that patients with inactive HDV infection had a significant T-cell proliferation response to HDV synthetic peptides; conversely, patients with active HDV-related hepatitis showed no significant response. 13 It is thus postulated that the host immune response might determine disease activities after HDV infection. 13 Augmentation of the host' s cellular immune response may represent an ideal way to treat chronic HDV infection.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…HDV genotype 1 is not cytopathic and thus immune responses probably play an important role in the pathogenesis of HDV-induced liver disease. In a study from Italy, patients with inactive but not active-HDV disease displayed HDV-specific proliferative CD4 responses to HDAg, suggesting that cellular immune responses probably controlled HDV infection (20). Preliminary data suggest that the endogenous interferon (IFN) system is highly activated in hepatitis D. This is supported by results showing that perforin-expressing lymphoid cells including CD4 1 T cells are more frequent in hepatitis D patients than in HBV or HCV monoinfection (21).…”
Section: Immunopathogenesis Of Hepatitis Dmentioning
confidence: 99%
“…PPD and Parj1-specific TCCs were derived from peripheral blood mononuclear cells (PBMCs) of a normal donor and maintained in culture as described previously (39) with some variations. In particular, cultures were set up in the presence or absence of 100 U/ml IL-4 (40) to obtain Th2 TCCs.…”
Section: Generation Of Antigen-specific Tccsmentioning
confidence: 99%